Methods of analysis of linear integer decoding pseudo-random codes - Tamila Valerievna Lavrovska; Sergey Gennadiyevich Rassomakhin; Aleksandr Olegovich Malofey (Наука. Инновации. Технологии)
Scientific and technical and social and economic progress changed life of millions of people, it has given boundless opportunities for receiving and information exchange. However, in this regard the number of technical means of processing and information transfer increases from year to year. This problem results in need of development of technologies for rational using of radio-frequency resource. Today pseudorandom coding is almost only way for support of required level of noise protection of confidential information. Advantages of use of pseudorandom codes which will allow to lower channel costs of transmission, but will allow to increase speed significantly are given. But today this technology isn't applied because decoding of such codes is connected to use of the rule of maximum likelihood. For blocks 20-30 channel characters is computationally infeasible. The method of decoding of pseudorandom codes on the basis of application of a method of branches and boundaries is offered.